Identification of potential early maturing single cross maize (Zea mays) hybrids - KUMAR, JYOTI; GADAG, RN; JHA, G K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during the winter season 2000-2001 and the rainy season of 2001 at IARI, New Delhi To analyze genetic components determining yield contributing traits in the 45 experimental crosses and to identify early maturing elite tnaize (Zea mays L.) hybrids among them These crosses were developed from 10 parentallines (DMB101-’DMB110) following diallel mating design (without reciprocals). While ’DMBI05’ was good general combiner for yield and the related traits, ’DMB109’ was involved in majority of.the elite cross combinations. The performance of ’DMBIOI’ x ’DMB 109’ was better in both (Delhi and Karnal) locations. On the basis of various parameters, 6 additional potential hybrids (’DMB103’ x ’DMBI04’, ’DMBI03’ x ’DMBIIO’, ’DMBI05’ x ’DMBI09’, ’DMB107’ x ’DMB109’, DMB102’ x ’DMB109’ and ’DMB103’ x ’DMB109’) were identified for further multilocation evaluations.